Strengthening a provincial program for scaling community-based resource management in Solomon Islands - Notere Boso, Delvene; Buga, Ben; Houma, Jill; Isihanua, Mathew; Jasper, Martin; Kenilorea, Peter; Konomalefo, Alick; Laumani, Michael; Saeni-Oeta, Janet; Siota, Faye Aborina; Sukulu, Meshach; Eriksson, Hampus (WorldFish, 2024)
This report summarizes the strengthening of a provincial program for community-based resource management (CBRM) with the Malaita Provincial Government. We describe the implementation and its costs to arrive at lessons learned that can guide future CBRM scaling up in other provinces. The role of provincial fisheries officers (PFOs) has been consistently overlooked and undervalued in internationally organized projects and programs, despite their mandated role in the Fisheries Management Act 2015. Over 4 years, a CBRM program was developed and implemented as a partnership between the Ministry of Fisheries and Marine Resources (MFMR), Malaita Provincial Government and WorldFish. A total of 96 communities were visited with information and awareness-raising about CBRM, as well as a survey component to ascertain current CBRM practices. As of December 2023, eight management plans had been developed by 32 communities that wanted to follow up on the information provided. In addition, the program used a CBRM monitoring and evaluation tool and trained 72 community facilitators representing 51 communities. The report provides reflections and lessons from the implementation of this program.